Physiological and Biochemical Responses in Two Ornamental Shrubs to Drought Stress - Toscano, Stefania; Farieri, Elisa; Ferrante, Antonio; Romano, Daniela (Frontiers in Plant Science, 2016)
Drought stress is one of the most important abiotic stress limiting the plant survival and growth in the Mediterranean environment. In this work, two species typically grown in Mediterranean areas with different drought responses were used. Two shrubs, with slow (Photinia ×fraseri Dress ‘Red Robin’) or fast (Eugenia uniflora L. ‘Etna Fire’) adaptation ability to drought, were subjected to three water regimes: well watered (WW), moderate (MD) and severe (SD) drought stress conditions for 30 days. Net photosynthetic rate, stomatal conductance, maximum quantum efficiency of PSII photochemistry (Fv/Fm), relative water content (RWC), chlorophyll content, proline, malondialdehyde (MDA) and antioxidant enzyme activities (superoxide dismutase, catalase and peroxidase) were measured. Results showed that RWC and proline were higher in Eugenia than in Photinia, demonstrating the greater tolerance of the latter to the water stress. The drought stress levels applied did not compromise photosynthetic efficiency through stomatal regulation, while a reduction of Fv/Fm ratio was observed at the end of the experimental period. MDA significantly increased after 30 days in both species. The antioxidant enzyme activities showed different responses to water stress conditions. In both species, the water stress scores showed positive, while proline content showed negative correlations with all physiological parameters.